CdS nanocages@defective-CoNi-LDH with bilayer porous hollow frameworks toward optimized sono-photocatalytic performance. Issue 31 (21st July 2022) - Fang, Bin; Xing, Zipeng; Du, Fan; Kong, Weifeng; Li, Zhenzi; Zhou, Wei
Abstract : HCNs@HD-CoNi-LDH are fabricated via Cd-based Prussian blue analog nanocubes twice sulfidation and epitaxial growth ZIF-67 etching into hollow defective CoNi-LDH strategies, which exhibit excellent sono-photocatalytic performance due to special bilayer porous hollow frameworks. Abstract : Sono-photocatalysis is considered a promising strategy for water decontamination and hydrolysis, and it is crucial to improve the sensitivity of the catalyst to mechanical forces to obtain more energy. In a single photocatalyst, the hollow structure refracts sunlight many times to improve light utilization, but with a sono-photocatalyst, can the hollow structure refract sound waves to enhance the sound field energy? This paper reports formation of CdS with different structures by controlling the etching rate and wrapping with hollow defective CoNi-LDH (HD-CoNi-LDH) to form a bilayer porous hollow framework structure. Characterization confirmed that evolution of CdS from the solid gave the bilayer a hollow framework state and improved the degree of sound field energy absorption. It was further shown that the honeycomb-like porous structure of HD-CoNi-LDH enhanced sound field energy absorption, which then acted on CdS to enable piezoelectric photocatalysis. Specifically, strong sound field absorption by hollow CdS@HD-CoNi-LDH increased the hydrogen precipitation rate by 3.5 times and the degree of bisphenol A degradation by approximately 30% compared to solid CdS. This work provides a new perspective for sono-photocatalysis.